Cytotoxicity of All-Trans-Retinal Increases Upon Photodegradation - Różanowska, Małgorzata (2012)
All-trans-retinal (AtRal) can accumulate in the retina as a result of excessive exposure to light. The purpose of this study was to compare cytotoxicity of AtRal and photodegraded AtRal (dAtRal) on cultured human retinal pigment epithelial cells in dark and upon exposure to visible light. AtRal was degraded by exposure to visible light. Cytotoxicity was monitored by imaging of cell morphology, propidium iodide staining of cells with permeable plasma membrane and measurements of reductive activity of cells. Generation of singlet oxygen photosensitized by AtRal and dAtRal was monitored by time-resolved measurements of characteristic singlet oxygen phosphorescence. Photodegradation of AtRal resulted in a decrease in absorption of visible light and accumulation of the degradation products with absorption maximum at ~330 nm. Toxicity of dAtRal was concentration-dependent and was greater during irradiation with visible light than in dark. DAtRal was more cytotoxic than AtRal both in dark and during exposure to visible light. Photochemical properties of dAtRal indicate that it may be responsible for the maximum in the action spectra of retinal photodamage recorded in animals. In conclusion, photodegradation products of AtRal may impose a significant threat to the retina and therefore their roles in retinal pathology need to be explored.